2021
DOI: 10.1145/3439717
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cultural Preferences for Social Robots

Abstract: This article presents a study of cultural differences affecting the acceptance and design preferences of social robots. Based on a survey with 794 participants from Germany and the three Arab countries of Egypt, Jordan, and Saudi Arabia, we discuss how culture influences the preferences for certain attributes. We look at social roles, abilities and appearance, emotional awareness and interactivity of social robots, as well as the attitude toward automation. Preferences were found to differ not only across cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 32 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…In our results, the gender identity of the stakeholders did not affect their views on robots in education. These results are in line with Korn et al (2021) who found similar results. Also, de Jong et al (2021) and Spence et al (2018) found that gender did not significantly predict attitudes toward social robots.…”
Section: Distinct Attitude Profiles Related To the Moral Considerationssupporting
confidence: 93%
See 2 more Smart Citations
“…In our results, the gender identity of the stakeholders did not affect their views on robots in education. These results are in line with Korn et al (2021) who found similar results. Also, de Jong et al (2021) and Spence et al (2018) found that gender did not significantly predict attitudes toward social robots.…”
Section: Distinct Attitude Profiles Related To the Moral Considerationssupporting
confidence: 93%
“…People with a low or medium income were more likely to belong to the attitude profile of Sceptic stakeholders, compared to stakeholders with a high income. Earlier research on the acceptance of social robots found that preferences were independent of participants' level of income (Korn et al, 2021). However, in the study of Korn et al (2021), most participants were students of similar ages and levels of income.…”
Section: Distinct Attitude Profiles Related To the Moral Considerationsmentioning
confidence: 88%
See 1 more Smart Citation
“…We observed a slight increase of the number of studies published during the second period of time (2014,2017] compared to the first period. For many years, robots have been tools used primarily in factories [72]. Nowadays, robots have become embedded in everyday people's life and co-operate in both the industrial and service sectors.…”
Section: Rq1: What Has Been Studied About User Experience In Social Robots Operating In Different Domains?mentioning
confidence: 99%
“…There has been therapeutic robot research done in the past to facilitate the elderly with AD, such as assistive robots for AD and related Dementia patients (6), and healthcare robots for older people at home (7). Several have highlighted that affective and social characteristic are important human attributes for machine behaviour (8), and have emphasized the aspect of human emotion or affect in robot interaction (9)(10)(11)(12). Thus, the research argues that assistive robots must prioritize this important element of human emotion in their design, so that effective strategies to positively influence the elderly emotions could be devised.…”
Section: Introductionmentioning
confidence: 99%